2011
DOI: 10.1038/nrneurol.2010.180
|View full text |Cite
|
Sign up to set email alerts
|

ATP7A-related copper transport diseases—emerging concepts and future trends

Abstract: This Review summarizes recent advances in understanding copper-transporting ATPase 1 (ATP7A), and examines the neurological phenotypes associated with dysfunction of this protein. Involvement of ATP7A in axonal outgrowth, synapse integrity and neuronal activation underscores the fundamental importance of copper metabolism to neurological function. Defects in ATP7A cause Menkes disease, an infantile-onset, lethal condition. Neonatal diagnosis and early treatment with copper injections enhance survival in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
478
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 535 publications
(490 citation statements)
references
References 152 publications
5
478
2
5
Order By: Relevance
“…There is a high degree of clinical variability among patients (48) and mutation analysis of ATP7A and ATP7B has identified ϳ160 and 300 patient mutations for each gene, respectively (Wilson Disease Mutation Database, University of Alberta) (64). It has been suggested that the clinical outcome depends on the type of mutation (8,11,48). Individuals with identical mutations, including twins (65) and also between family members, can have vastly different clinical phenotypes (66,67), which suggests that other factors are involved in determining the clinical outcome of Menkes and Wilson diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a high degree of clinical variability among patients (48) and mutation analysis of ATP7A and ATP7B has identified ϳ160 and 300 patient mutations for each gene, respectively (Wilson Disease Mutation Database, University of Alberta) (64). It has been suggested that the clinical outcome depends on the type of mutation (8,11,48). Individuals with identical mutations, including twins (65) and also between family members, can have vastly different clinical phenotypes (66,67), which suggests that other factors are involved in determining the clinical outcome of Menkes and Wilson diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Defective copper transport across the basolateral membrane of these cells into the portal circulation leads to a systemic copper deficiency with devastating consequences (3,4,9,10). Biochemical abnormalities lead to neurological and developmental defects among many other symptoms (9,11). WD is an autosomal recessive copper toxicity disorder (9).…”
mentioning
confidence: 99%
“…XLCL is caused by mutations in ATP7A, a copper transporter gene. 3,4 Diagnosis can be made based on clinical features, low serum levels of copper and ceruloplasmin and mutation analysis. 3,4 In autosomal dominant CL (MIM 123700), the family history, the appearance of skin signs and organ involvement is variable.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the closely related ATPase ATP7B, ATP7A is a critical transporter of copper. Mutation of ATP7A is known to cause at least three distinct disorders (24), including Menkes disease (25)(26)(27), occipital horn syndrome (considered to be a milder form of Menkes disease) (28), and isolated distal motor neuropathy (29). Conversely, mutation of ATP7B causes Wilson disease (30,31), which is characterized by neuronal and hepatic pathologic processes associated with copper accumulation.…”
mentioning
confidence: 99%